2016
DOI: 10.1007/s40778-016-0031-y
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Opportunities to Harnessing the (Hematopoietic) Stem Cell Niche

Abstract: In our body, stem cells reside in a microenvironment termed the niche. While the exact composition and therefore the level of complexity of a stem cell niche can vary significantly tissue-to-tissue, the stem cell niche microenvironment is dynamic, typically containing spatial and temporal variations in both cellular, extracellular matrix, and biomolecular components. This complex flow of secreted or bound biomolecules, cytokines, extracellular matrix components, and cellular constituents all contribute to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 115 publications
0
21
0
Order By: Relevance
“…The explicit role matrix ligands play in modulating HSC fate decisions has remained largely unknown because of the complexity of the matrix surrounding HSCs in vivo ( 22 , 39 ). Previous reports have suggested that ECM components, such as matrix proteins (for example, fibronectin, collagen, laminin, and osteopontin) and proteoglycans, may affect hematopoiesis and HSC function in vivo; further, matrix proteins, such as fibronectin and collagen, have been shown to induce adhesion-mediated morphological changes in HSCs in vitro ( 22 , 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…The explicit role matrix ligands play in modulating HSC fate decisions has remained largely unknown because of the complexity of the matrix surrounding HSCs in vivo ( 22 , 39 ). Previous reports have suggested that ECM components, such as matrix proteins (for example, fibronectin, collagen, laminin, and osteopontin) and proteoglycans, may affect hematopoiesis and HSC function in vivo; further, matrix proteins, such as fibronectin and collagen, have been shown to induce adhesion-mediated morphological changes in HSCs in vitro ( 22 , 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…With entering the 21st century, artificial 3D culture environments have greatly improved with respect to their efficiency, versatility and robustness, hence providing dynamic systems with the ability to address many, if not all, fundamental questions about biomaterial regulation of live stem cell fate and function . Of particular interest, recent advances in fabrication approaches at the micro‐ and nanoscale have allowed biomedical scientists to capture and engineer the complexity and repertoire of the ECM in 3D cell culture platforms with complex flow of ECM components, cellular constituents, and secreted or bound biomolecules and cytokines in vitro …”
Section: Engineering a 3d Home For Cell Accommodationmentioning
confidence: 99%
“…However, if the aim is the generation of tissue‐ and organ‐like structures for reconstructive purpose, higher complexity levels of biomaterial systems (such as in vitro 3D culture models and in situ biosensing tools) presenting physicochemical and biological cues in a temporospatial manner are absolutely justified . We expect that the future 3D tools and systems will be capable of inducing tissue‐specific cell differentiation, modulating cell geometry and monitoring cellular responses, among others; generate new insights into fundamental cellular behavior information; and lead to more and more biomedical applications ranging from 3D cell culture and production, stem cell therapy, and tissue engineering to drug discovery and development …”
Section: Engineering a 3d Home For Cell Accommodationmentioning
confidence: 99%
“…Prior to cleavage, the solution was diluted to 2 M urea with 100 mM ammonium bicarbonate at pH 8. Proteins were cleaved via trypsin (Thermo) and Lys-C endoproteinase (Promega, Madison, WI), at a ratio of 1:50 enzyme to protein overnight (12)(13)(14)(15)(16) hours) at 37°C. Samples were cleaned and concentrated using a C18 column (Thermo).…”
Section: Mass Spectrometrymentioning
confidence: 99%
“…For example, protein composition and tissue stiffness are important for cellular processes like migration and proliferation 7,89 , as well as regulating stem cell fate and organoid development [10][11][12] . Thus, it is not surprising that the surrounding extracellular matrix (ECM) plays a key role in the proper function of bone marrow because both hematopoietic and stromal progenitor cells originate from this tissue 13 . For example, both bone marrow stiffness and fibronectin are important for the maintenance of hematopoietic stem cell progenitors 14 .…”
mentioning
confidence: 99%